An investigation of dark soliton behaviors within the nonlinear micro and nano ring resonators - Sangwara, N.; Teeka, C.; Pipatsart, S.; Yupapin, P. P. (My University, 2010)
We firstly propose the interesting results of a dark soliton pulse propagating within the nonlinear micro and nano waveguides. The system consists of nonlinear micro and nano ring resonators, whereas the dark soliton is input into the system and traveling within the waveguide. A continuous dark soliton pulse is chopped to be the smaller pulses by the nonlinear effects known as chaos. The nonlinear behaviors such as chaos, bistability and bifurcation are analyzed and discussed. The power amplification is the property that can be used to perform the long distance link, where the security is the dominant reason. © 2009 Elsevier GmbH. All rights reserved.
Keywords: Dark soliton; Nonlinear optics; Nonlinear ring resonator; Nonlinear waveguide